A test in literature for measuring reading skills of high school teachers of English - Mendoza, Milagros C. 1928-
A test in literature was designed in this study to measure the reading skills of English high school teachers. The study measured the following reading skills: vocabulary skills, interpretative skills, critical skills, comprehension of a dialogue (integrated skills), and interpretation of a poem (integrated skills).